LONG-TERM EFFECTS EVALUATION OF USING ARTIFICIAL INTELLIGENCE-BASED AUTOMATED LEARNING SYSTEMS IN IMPROVING ENGLISH CONTENTUNDERSTANDING AT THE SECONDARY EDUCATION LEVEL - Yulian Purnama; Fini Widya Fransiska; Ali Muhdi; Muflihah; Fitria Meisarah (Indonesian Journal of Education (INJOE), 2024)
This longitudinal study thoroughly examined the enduring impacts of Artificial Intelligence (AI)-based automated learning systems on enhancing English content understanding among secondary education students. Employing a quasi- experimental research design, participants were randomly assigned to experimental and control groups. The study spanned multiple academic terms, providing an extensive timeframe for evaluating the sustained effects of AI integration. The research incorporated diverse methodologies, including pre-test and post-test assessments, continuous monitoring of AI-based learning activities, and surveys/interviews with participants. The findings revealed substantial improvements in English content understanding among students exposed to AI- driven learning systems over an extended period. Cognitive development analyses demonstrated not only enhanced language proficiency but also improvements in broader cognitive skills. Behavioral changes, including heightened engagement, were noted, positively impacting the learning experience. The study critically compared its outcomes with previous research, contributing valuable insights to the evolving discourse on the long-term effects of AI in education. Implications for long- term AI integration in English education were discussed, considering pedagogical shifts, curriculum development, and ethical considerations. The study identified potential areas for future research, emphasizing the need for continued exploration in optimizing AI's role in education. Recommendations were provided for educators, policymakers, and developers to inform evidence-based practices. In conclusion, this research comprehensively explains the sustained benefits and challenges associated with AI-based automated learning systems in secondary education.